2014
DOI: 10.1093/eurheartj/ehu102
|View full text |Cite
|
Sign up to set email alerts
|

The natural and unnatural history of the Mustard procedure: long-term outcome up to 40 years

Abstract: Long-term survival after Mustard repair is clearly diminished and morbidity is substantial. Early postoperative arrhythmias are a predictor for heart failure and late arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
125
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(140 citation statements)
references
References 30 publications
13
125
0
2
Order By: Relevance
“…These include systemic venous and pulmonary venous channel obstruction, atrial baffle leak, sick-sinus syndrome and atrial tachyarrhythmias 44. In a long-term outcome study up to 40 years of patients after the Mustard procedure for d-TGA, long-term survival was diminished and morbidity substantial 45. The cumulative incidence of reinterventions was 46%, mainly for baffle stenosis or leakage.…”
Section: Postsurgical Outcomesmentioning
confidence: 99%
“…These include systemic venous and pulmonary venous channel obstruction, atrial baffle leak, sick-sinus syndrome and atrial tachyarrhythmias 44. In a long-term outcome study up to 40 years of patients after the Mustard procedure for d-TGA, long-term survival was diminished and morbidity substantial 45. The cumulative incidence of reinterventions was 46%, mainly for baffle stenosis or leakage.…”
Section: Postsurgical Outcomesmentioning
confidence: 99%
“…Due to extensive scarring, patients with transposition of the great arteries (TGA) and atrial switch surgery have a high incidence of atrial arrhythmias 11. Approximately 30% of patients after Mustard or Senning repair develop atrial arrhythmias within 10 years,5 and 28%–40% within 30–35 years after surgery 12 13. With the advent of the arterial switch surgery that does not require atrial incisions, SVT incidence has dropped to approximately 5% 14 15…”
Section: Pathophysiology Of Svt In Achdmentioning
confidence: 99%
“…3-13 Atrial tachyarrhythmia has been reported as the most common early clinical complication, 5,7,11,13,14 is associated with significant clinical morbidity, has been suggested to reflect systemic RV dysfunction, and is a recognized marker of elevated atrial pressure and increased mortality. 5,7,13,15 Thereafter, RV dysfunction precedes the onset of symptoms, clinical heart Background-We hypothesized that fibrosis detected by late gadolinium enhancement (LGE) cardiovascular magnetic resonance predicts outcomes in patients with transposition of the great arteries post atrial redirection surgery.…”
mentioning
confidence: 99%